Prevention of adhesive capsulitis following pacemaker implantation: A randomized controlled study. Issue 9 (13th August 2020) - Jorat, Mohammad Vahid; Namayandeh, Seyedeh Mahdieh; Mehdipour Namdar, Zahra; Aslani, Amir
Abstract: Introduction: Gradual painful loss of active and passive range of motion in shoulder joint was introduced as adhesive capsulitis (AC). Disabilities in patients with AC are absenteeism from work, loss to leisure time, and recurrent seeking to health care services. The aim of this study was to evaluate the incidence of AC following pacemaker implementation. The effect of physical therapy and exercise education was also evaluated to prevent AC following pacemaker implementation. Methods: This study is a randomized clinical controlled trial. It was conducted on 62 pacemaker candidates. Patients with no shoulder pain and without any motion limits were enrolled in the study consecutively. The patients randomly were divided into two groups after pacemaker implementation. One group was treated with physical therapy (group A, n = 28) and the other group did not (group B, n = 34). The incidence of AC was assessed in both groups after 4 months. Results: A total of 62 patients were enrolled in the study. The mean age was 63.2 ± 12.1 years in the group A and 67.1 ± 17.6 years in the group B. Age was not significantly different between groups. A total of 11 patients (17.7%) had AC 16 weeks after the initial visit (two patients in group A and nine patients in group B; P = .004). Conclusions: Incidence of AC is 17.7% following device implantation. Exercise education and physical therapy significantly reduces AC incidence following pacemaker implantation.